Delaying Integration of Immigrant Labor for the Purpose of Taxation - Wolfram F. Richter (Center for Economic Studies and ifo Institute (CESifo), 2002)
Delayed Integration (DI) is a rule for taxing migrants. It requires that immigrants be taxed in the receiving country only after some period of transition. Conversely, emigrants are released from the obligation to pay home taxes only after a certain period. DI is an alternative to the Employment Principle and the Origin Principle. The former governs the international taxation of labor while a close substitute to the latter - the Nationality Principle - is underlying U.S. tax law. The paper studies the potential merits of DI in a setting which allows one to trade off the social cost of tax distortion and the social cost of wasteful government.
Keywords: 330